Fast fashion retailer’s marketing strategies: brand awareness and customer brand engagement - Moreira, Rodrigo da Mota (2020)
This study is an exploratory study, with a quantitative approach, carried out through a survey, applied through a questionnaire using an online tool, aimed at consumers in the clothing / fashion sector in France. Its central objective is to understand customer involvement with two brands that have different marketing strategies. Two of the world's largest brands were selected, H&M and Zara. It was observed that while the company H&M invests in traditional advertising and acts strongly with the involvement of its audience in the online environment, seeking to establish links and add value to customers. The company Zara chooses to invest little in marketing and work with market expansion strategies, seeking to establish itself physically in a greater number of countries, showing the greater recognition of the brand. The results obtained allowed us to verify that although companies have similar results, the company that adopts greater engagement with the client tends to stand out, regardless of the strategy that it uses for this engagement to occur.